Regional Economic Outlook, October 2007, Sub-Saharan African. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2007)
The region's prospects look strong. Growth in sub-Saharan Africa should reach 6 percent in 2007 and 6 3/4 percent in 2008. The economic expansion is strongest in oil exporters but cuts across all country groups. This would extend a period of very good performance. In recent years, sub-Saharan Africa has been experiencing its strongest growth and lowest inflation in over 30 years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet